Anti-Communism Politics: The Study of Communism Discourse on the Indonesian Anti-Communist Front (FAKI) of Yogyakarta City - Alam Mahadika; David Efendi (Journal of Government and Political Issues, 2021)
This research tried to raise the issue of communism regarding anti-communist politics in the perception of the Indonesian Anti-Communist Front of Yogyakarta City and its strategy to understand and the movement of communism. This field research with a qualitative approach in this research is outlined using qualitative descriptive methods. The research findings showed that the Indonesian Anti-Communist Front of Yogyakarta City has a strategy of resistance to communism by organizing rallies and even rallies always collaborating with other nationalist community organizations. FAKI Yogyakarta also always holds an annual event that commemorates Pancasila day by watching G30S/PKI films together to grow the nation's knowledge, especially the younger generation of strategy. The next is to oversee discussions that smell communist and views on politics and religion, The Discourse of the Indonesian Anti-Communist Front Yogyakarta city given the political movement of communism is In the power struggle my words about the Indonesian Communist Party is the goal of justifying various ways to achieve the desire for power (Politics), the goal of justifying all means. The discourse of the Indonesian Anti-Communist Front of Yogyakarta city views communist social viewpoints and beliefs consistent with its historical methods. Communists view religion as a result of the history of human development. Based on historical materialism, the beginning of religion was designed by man as an institution containing all aspects of goodness, beauty, justice, and the realm of Communists viewing religion as a human creation. Religion is an imaginary world. Communism, which has a very heinous problem with theology, causes distrust of God and even causes them to be anti-God, anti-Religion, and even aggressive towards religious groups. But part of the Indonesian Communist Party cadre is Islamic, so what the Indonesian Anti-Communist Front says does not represent a diverse reality about PKI and communism.